PENGARUH MOTIVASI DAN DISIPLIN TERHADAP PRODUKTIVITAS PEGAWAI PADA BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN BOLAANG MONGONDOW - Mokoginta, Jumie S L.; Soegoto, Agus Supandi; Manoppo, Erna; Mokoginta, Sicilya C.; Manoppo, Endah (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Motivation is an encouragement made by others so that existing employees want to work and produce something better. Discipline is the behavior that exists in the employee concerned to obey all the rules that exist in the organization. The purpose of this study was to determine the effect of motivation and discipline both simultaneously and partially affecting the work productivity of employees at the Regional Disaster Management Agency of Bolaang Mongondow Regency. The type of research used is associative research with Multiple Linear Regression analysis methods. The number of samples used was 30 respondents. The results showed that simultaneous and partial motivation and discipline affect work productivity. the leader can provide more motivation to the employees so that work productivity is further improved in the future.